Characterization of the Mammalian Post-mortem Thanatomicrobiome: A Time and Temperature Based Approach using Culture Dependent and Independent Techniques - Harshita Tiwari; Tripti Bhatnagar; Neeharika Srivastava (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: The thanatomicrobiome (Thanatos, Greek for death) or the postmortem microbiomes have been recognized as a significant biomarker to determine time and whereabouts of host death. The number and abundance of each organ’s signature microbioata can be of utmost importance to forensic microbiologists as a novel data source for estimating post-mortem interval. Method: Fresh samples of Liver and Kidney of goat were taken and processed. Cultures were prepared and incubated at varying temperatures (37°C, 27°C, and 4°C) in both aerobic and anaerobic condition. After every 24hour, the plates were observed to examine the growth for isolation of microbial colonies. Results: The present finding focuses on the characterization of various thanatomicrobiome compositions across time, temperature and oxygen availability once the animal is passed out. Conclusion: In the present study it was found that increase in time after death leads to variation in bacterial culture in the internal tissues of body which helps in estimation of Post-mortem interval (PMI) in different conditions (such as aerobic and anaerobic), and at different storage temperature.